2019
DOI: 10.1016/j.physio.2018.11.303
|View full text |Cite
|
Sign up to set email alerts
|

Physical prognostic factors predicting outcome following lumbar discectomy surgery: systematic review and narrative synthesis

Abstract: Background: Success rates for lumbar discectomy are estimated as 78-95% patients at 1-2 years post-surgery, supporting its effectiveness. However, ongoing pain and disability is an issue for some patients, and recurrence contributing to reoperation is reported. It is important to identify prognostic factors predicting outcome to inform decision-making for surgery and rehabilitation following surgery. The objective was to determine whether pre-operative physical factors are associated with post-operative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Relevance of several of the identified predictors was also supported by previous research on patient-reported outcomes from the Spine Tango registry in other countries (Sobottke et al, 2017; Staub et al, 2020). Our results are also consistent with systematic reviews supporting prognostic value of age, preoperative pain intensity and disability, type of spinal pathology, previous surgeries, and smoking (Dorow et al, 2017; Halicka et al, under review ; Rushton et al, 2018; Wilhelm et al, 2017; Wilson et al, 2016). In contrast, we did not find any effect of symptom duration, here recorded indirectly as treatment duration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Relevance of several of the identified predictors was also supported by previous research on patient-reported outcomes from the Spine Tango registry in other countries (Sobottke et al, 2017; Staub et al, 2020). Our results are also consistent with systematic reviews supporting prognostic value of age, preoperative pain intensity and disability, type of spinal pathology, previous surgeries, and smoking (Dorow et al, 2017; Halicka et al, under review ; Rushton et al, 2018; Wilhelm et al, 2017; Wilson et al, 2016). In contrast, we did not find any effect of symptom duration, here recorded indirectly as treatment duration.…”
Section: Discussionsupporting
confidence: 91%
“…Reliable predictive factors could maximise patient benefit and cost-effectiveness of surgery. Although several systematic reviews concluded that medical, sociodemographic, and psychological factors are linked to improvement in pain and disability following lumbar spine surgery (Dorow et al, 2017; Halicka et al, under review ; Rushton et al, 2018; Wilhelm et al, 2017; Wilson et al, 2016), we lack clear clinical guidelines on the reliable predictors (de Campos, 2017) and predictive factors are rarely formally documented.…”
Section: Introductionmentioning
confidence: 99%
“…Several health-related factors were identified as potential predictors of reduction in pain or disability after surgery. Previous systematic reviews concerned with this class of predictors focused only on disk herniation cohorts,15,18,19 thus our review extends the existing evidence synthesis to a broader range of spinal pathologies. In fact, the type of diagnosis itself may be an important predictor, as cohorts with spinal stenosis presented with less reduction in back and leg pain after surgery compared with degenerative disk disease and disk herniation cohorts (low-quality evidence).…”
Section: Discussionmentioning
confidence: 87%
“…For instance, fusion surgery for back pain has better outcomes if patients have successfully completed a pain management course with cognitive-behavioral therapy. 14 Previous systematic reviews addressing similar questions were restricted to specific pathologies such as disk herniation [15][16][17][18][19] or surgical interventions such as spinal fusion. [20][21][22] However, the prognostic value of sociodemographic, health-related, and psychological patient characteristics for reduction in pain and disability may be independent of medical diagnosis and type of surgery, and considering broader LBP population could potentially mitigate the issues of insufficient amount or quality of evidence faced by previous reviews.…”
mentioning
confidence: 99%
“…Identification of clinical predictors of outcome in these patients likely involves analysis of many potential interacting factors including psychological and cognitive‐behavioural factors such as fear avoidance behaviour, negative outcome expectancy (den Boer, Oostendorp, Beems, Munneke, & Evers, 2006a; den Boer, Oostendorp, Beems, Munneke, Oerlemans, et al, 2006; Johansson, Linton, Rosenblad, Bergkvist, & Nilsson, 2010), pain catastrophizing (Lautenbacher et al., 2010), depression, anxiety (Chaichana, Mukherjee, Adogwa, Chen, & McGirt, 2011) and physical factors (Rushton, Zoulas, Powell, & Staal, 2018; Werner et al., 2017). While such multidimensional predictors of outcome to inform surgical patient selection are valuable and may guide alternative clinical pathways of care, the predictive value of sensory nerve fibre function has yet to be systematically investigated in people with painful lumbar radiculopathy.…”
Section: Introductionmentioning
confidence: 99%